The Three Similes: A Comparative Analysis of the Sanskrit and Pali Sources - Wolf, Chris (Buddhist Studies Review, 2024)
In accounts of the Bodhisattva’s search for enlightenment, three similes come to his mind. In them, the requirement for physical and mental seclusion in the attainment of enlightenment is compared to a man who wants to light a fire by three different means. However, when comparing the different versions of these similes, one finds that they serve different and opposing purposes. The task of the current paper is to shed some light on the numerous variations in different occurrences of these three similes, to determine their purpose and their most appropriate place within the Buddha’s biographical narrative. I attempt this through a text-critical analysis and comparison of all versions available in their original Indian languages. The analysis shows that the similes do not fit best in the context of teaching about self-mortification in which they usually appear, but in the context of the Bodhisattva’s discovery of the path to enlightenment.